Electrochemically Deposited rGO Cu2S Composite as a High-Performance Counter Electrode for Quantum Dot-Sensitized Solar Cells - Duyen, Nguyen Thuy Kieu; Hanh, Nguyen Thi My; Hieu, Le Van; Luu, Thi Viet Ha; Dang, Huu Phuc (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
This study reports the development of reduced graphene oxide (rGO), copper sulfide (Cu2S), and their hybrid composite (rGO-Cu2S) as counter electrodes (CEs) for quantum dot-sensitized solar cells (QDSSCs). The electrodes were fabricated on FTO substrates via a simple, low-temperature electrochemical deposition method. Morphological analysis revealed flower-like Cu2S nanostructures and wrinkled rGO sheets, while the composite combined these features into a uniform hybrid layer. Electrochemical measurements demonstrated that the rGO-Cu2S CE exhibited superior catalytic activity and lower charge-transfer resistance compared to the individual materials. When integrated into QDSSCs, the rGO-Cu2S electrode achieved the highest power conversion efficiency (4.65%), outperforming Cu2S (3.77%) and rGO (3.24%). The synergistic interaction between conductive rGO networks and catalytically active Cu2S nanostructures underpin this improvement, highlighting rGO-Cu2S as a cost-effective and efficient alternative to noble-metal-based counter electrodes.